Interactive Learning Media With Augmented Reality (AR) Geogebra for Teaching Geometry in Elementary School - Buchori, Achmad; Sulianto, Joko; Osman, Sharifah (Universitas Muhammadiyah Surakarta, 2023)
In Semarang's elementary maths education, augmented reality (AR) and three-dimensional tech are underused in geometry instruction. These technologies promise an engaging and interactive presentation of three-dimensional objects. Presently, educators are confined to traditional tools like PowerPoint, providing a less immersive learning experience. This study addresses this gap with AR Geogebra, a tailored interactive tool for geometry instruction. Developed using the ADDIE model, the study involved fifty fifth-semester university students. Notably, material and media validation scored 90%, deeming it